Profiling the serum proteome during Schistosoma mansoni infection in the BALB/c mice: A focus on the altered lipid metabolism as a key modulator of host-parasite interactions - Gonçalves-Silva, Gustavo; Vieira, Lara Geralda Magela dos Santos; Cosenza-Contreras, Miguel; Souza, Ana Flávia Pinho; Costa, Daniela Caldeira; Castro-Borges, Wiliam (Frontiers in Immunology, 2022)
Schistosomiasis represents a condition in which every aspect of the disease, starting from skin invasion of the cercariae to egg laying by adult worms, incites a tissue response from the vertebrate host. This response, whether acute or chronic, leads to the appearance of reporter molecules of tissue injury in bodily fluids that could be surveyed as markers for disease diagnosis, status and prognosis. In this scenario, the serum proteome associated with a schistosome infection remains poorly explored; particularly by the use of high-throughput mass spectrometric instrumentation. In this study, we aimed to comparatively examine the serum proteome of control versus infected BALB/c mice, spanning the interval between the onset of egg laying and the peak of the acute phase of infection. Compositional analysis of the sera, using one dimensional reversed-phase fractionation of tryptic peptides coupled to mass spectrometry, allowed identification of 453 constituents. Among these, over 30% (143 molecules) were differentially present comparing sera from infected and non-infected mice, as revealed by quantitative label-free shotgun approach. The majority of proteins exhibiting altered levels was categorised as belonging to immune response (acute phase-related proteins) followed by those linked to lipid transport and metabolism. Inspection of the lipid profile from control and infected individuals demonstrated more pronounced and significant alterations in triglycerides, VLDL and HDL fractions (p<0,001), attesting for a disturbance in circulating lipid molecules, and suggesting a key role in hostparasite interactions. Our findings provide a global view of the serum proteome in the context of experimental schistosomiasis during the acute phase of infection. It contributes by listing key molecules that could be monitored to inform on the associated inflammatory disease status. We hope it will shed light into uncovered aspects of the Schistosoma mansoni parasitism in the vertebrate host, particularly those related to modulation of the lipid metabolism mediating immune responses.